1999
DOI: 10.1007/s004240050814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the protein kinase A inhibitor H-89 on Ca 2+ regulation in isolated ferret ventricular myocytes

Abstract: We investigated the effects of a protein kinase A (PKA) inhibitor, H-89 {N-[2-(p-bromocinnamylamino)ethyl]-5-iso-quinolinesulphonamide}, on Ca2+ regulation in Fura-2-loaded ferret myocytes. H-89 (10 micromol/l) decreased the amplitude of the Fura-2 transient to 28. 2+/-4.3% (P<0.001) of control and prolonged its duration, characterized by a decrease in the rate of decline of Ca2+ to diastolic levels: t1/2 increased from 311+/-35 ms to 547+/-43 ms (P<0.001, n=7). Reduced Ca2+ uptake by the sarcoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…We previously reported that, in a rat model of STZ-induced diabetes, a prominent abnormal Ca 2ϩ leak occurs through the RyR2, owing to a partial loss of RyR2-bound FKBP12.6 and PKA-mediated hyperphosphorylation of RyR2 (51). Both protein kinases, PKA and PKC, are expressed in cardiac muscle (22), and they strongly controlled cardiac inotropic activity (17,19,45). PKA and PKC play a central role in transducing signal and potentiating intracellular cross talk by phosphorylating diverse substrates, including receptors, enzymes, and transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that, in a rat model of STZ-induced diabetes, a prominent abnormal Ca 2ϩ leak occurs through the RyR2, owing to a partial loss of RyR2-bound FKBP12.6 and PKA-mediated hyperphosphorylation of RyR2 (51). Both protein kinases, PKA and PKC, are expressed in cardiac muscle (22), and they strongly controlled cardiac inotropic activity (17,19,45). PKA and PKC play a central role in transducing signal and potentiating intracellular cross talk by phosphorylating diverse substrates, including receptors, enzymes, and transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar inhibitory actions of high H89 concentrations (100 ìM) on net Ca 2+ uptake by the SR and Ca 2+ sensitivity of the contractile apparatus in rat skinned fibers were observed by Blazev et al (7). The inhibitory effect of H89 on SR Ca 2+ uptake was also demonstrated in isolated ferret ventricular myocytes (36). In view of the above, the use of H89 as a tool to study the role of PKA-mediated phosphorylation on Ca 2+ regulation in myocytes, is limited by the non-specific effects of the drug on the SR Ca 2+ -ATPase.…”
Section: Lochner and J A Moolmanmentioning
confidence: 99%
“…The nature of such PKA-independent inhibitory actions of H-89 is unknown and may involve other kinases or even other direct/indirect nonspecific effects unrelated to channel phosphorylation. This is particularly likely given that the three K þ currents investigated in this study have markedly different structures at the molecular level and also because previous studies have already documented some other nonspecific effects of H-89 (Hussain et al, 1999;Blasev et al, 2001;Choi et al, 2001), which can only therefore be used as an invaluable tool if these other effects are carefully avoided.…”
Section: Discussionmentioning
confidence: 96%